Kinerja Bidang Pariwisata dalam Pengembangan Destinasi dan Industri Pariwisata pada Dinas Kebudayaan, Pariwisata, Pemuda dan Olahraga Kabupaten Katingan - Sabirin Muhtar; Muhammad Iqbal Nawawi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to provide an overview of the Performance of the Tourism Sector in Destination and Tourism Industry Development at the Katingan Regency Culture, Tourism, Youth and Sports Agency. The method used in this study is descriptive qualitative. Where is the technique of collecting data by observation, interviews, and documentation. Data analysis uses qualitative data analysis procedures, namely extracting meaning, drawing, explaining and placing data on their respective contexts. The results of the research show in this research are the Performance of Tourism in Destination and Tourism Industry Development at the Katingan Regency Office of Culture, Tourism, Youth and Sports. But the need for community participation in tourism development and the synergy of government programs and related institutions will be even better in developing tourism in Katingan Regency, because considering tourism in Katingan Regency is still virgin or still natural with objects in the form of lakes, mountains, rivers, rocks and others that are still natural.